Individuals With Autism Spectrum Disorder Show Altered Event-Related Potentials in the Late Stages of Olfactory Processing. (11th November 2019) - Okumura, Toshiki; Kumazaki, Hirokazu; Singh, Archana K; Touhara, Kazushige; Okamoto, Masako
Abstract: Atypical sensory reactivities are pervasive among people with autism spectrum disorder (ASD). With respect to olfaction, most previous studies have used psychophysical or questionnaire-based methodologies; thus, the neural basis of olfactory processing in ASD remains unclear. This study aimed to determine the stages of olfactory processing that are altered in ASD. Fourteen young adults with high-functioning ASD (mean age, 21 years; 3 females) were compared with 19 age-matched typically developing (TD) controls (mean age, 21 years; 4 females). Olfactory event-related potentials (OERPs) for 2-phenylethyl alcohol—a rose-like odor—were measured with 64 scalp electrodes while participants performed a simple odor detection task. Significant group differences in OERPs were found in 3 time windows 542 ms after the stimulus onset. The cortical source activities in these time windows, estimated using standardized low-resolution brain electromagnetic tomography, were significantly higher in ASD than in TD in and around the posterior cingulate cortex, which is known to play a crucial role in modality-general cognitive processing. Supplemental Bayesian analysis provided substantial evidence for an alteration in the later stages of olfactory processing, whereas conclusive evidence was not provided for the earlier stages. These results suggest that olfactory processing in ASD is altered at least at the later, modality-general processing stage.